Keberlanjutan Akses Air Bersih melalui Sumur Bor dan Pompa Air Tenaga Surya di Desa Bila Cenge - Andre Sugioko; Trifenaus Prabu Hidayat; Enny Widawati; Karel Octavianus Bachri (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2026)
Southwest Sumba Regency is located in the province of East Nusa Tenggara, part of the Sumba Islands, which are famous for their natural beauty. This area offers a unique combination of stunning landscapes, distinctive cultural richness, and community life that still upholds local traditions. However, behind all that, there are several fundamental problems that still occur in Southwest Sumba Regency, especially stunting. Stunting is the main problem in this location. Stunting is chronic malnutrition in toddlers, which results in stunted growth in both height and weight. One of the factors causing stunting is the lack of access to clean water and proper sanitation. Clean water is very important in maintaining personal hygiene, food, and the environment so that it can prevent various diseases that can inhibit children's growth. The construction of drilled wells is one effective solution to overcome the problem of access to clean water in areas prone to stunting. With the existence of drilled wells, the community will have easier access to clean water so that it can improve the quality of life and health, especially for children. From the identified problems, the solution offered is the procurement of drilled wells with solar-powered pumps (PLTS). Thus, the problem of access to clean water and energy sources to operate the drilled well can be resolved. Then it can be developed in various locations/areas that have not received access to water. The capacity of the drilled well that has been made produces an output of 50 liters/hour. This output has been in accordance with the target of devotion.